If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3x-2=4(x-2)9
We simplify the equation to the form, which is simple to understand
3x-2=4(x-2)9
Reorder the terms in parentheses
3x-2=+(+4x-8)*9
Reorder the terms in parentheses
3x-2=+(+36x-72)
Remove unnecessary parentheses
+3x-2=+36x-72
We move all terms containing x to the left and all other terms to the right.
+3x-36x=-72+2
We simplify left and right side of the equation.
-33x=-70
We divide both sides of the equation by -33 to get x.
x=2.1212121212121
| 9x^2+47x-42=0 | | (1-4i)(1+4i)= | | 4(-6)-2(1+6)= | | -2d^22f^12/c^36= | | 45=3-(2x-7) | | 5z-2(2z+1)=19 | | 4.5+4=0.6x-3 | | -8+5=313 | | 5x+1=-(4x-7) | | y-6=1/5(x-3) | | 11x-19=5(2x+5)-6 | | 2+4lnx=5 | | 55(x+2.5)=45*x | | 3-4a(11)=41 | | -9(3s+4)= | | X-2/3=1/6 | | 4x+17=2x-7 | | (2x^2-x-1)*(5-x^2)=0 | | 12w^2+9w= | | 5w^2+2w-63=0 | | 4x^2-9-2(2x-3)+x(2x-3)=0 | | B/15-19=-6 | | 4/(6-) | | 10-1x-(-2)-8+4x= | | 2(90-x)=3(90-2x) | | (X^2-12)+(3x+6)=x | | 4z-6=6z-3z | | 6x+7-8(x+1)=5x+4 | | 90-2x=x | | 2(4-3x)-5=33 | | 8.4x+3.4y=5 | | 18a^2-3a=1 |